Environmental Theology and Worship Teaching of Lombok Wetu Telu Old Manuscripts - Abdul Quddus; Lalu Muhammad Ariadi; Sigit Wahyudi; Nurmaidah; Ika Juhriati (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
This study aims to explore the intertwining of two Islamic teachings, namely environmental values and worship practice in three old manuscripts popular among Wetu Telu people in North Lombok. It questions how the three, Serat Rengganis, Usada Rara, and Tuḥfah al-Mursalāh ilā Rūḥ an-Nabī deliver the teaching through its contents about the two themes. Those manuscripts are well known and routinely recited among Wetu Telu in Bayan, a village that routinely holds a ritual called pepaosan. The anthropological method used in this paper relies on primary data through in-depth observation, interviews with relevant parties, as well as manuscript content mapping. The finding shows that environmental values and worship teaching among Wetu Telu in North Lombok are mostly based on those manuscripts with Serat Rengganis as the mostly referred and popular one. The manuscripts likely use metaphors to deliver the teaching which makes it hard to understand the meaning without attending the pepaosan to listen to explanations from the experts. Integration of both teachings is mainly clear from how Wetu Telu people are supposed to behave well to God, fellow humans, and nature. Both individual and social worship of Wetu Telu, like ṣalāt (prayer) and al-ḥajj (pilgrimage), also indicate how the three old manuscripts still play an important role within the community.